Patterned colouring and shape memory effect of polyethylene terephthalate via thermo-mechanical treatment - Paramasilvam, Lingeyshwaran (Nanyang Technological University, 2022)
This study covers the experimental investigation of Polyethylene Terephthalate (PET) in terms of patterned colouring and shape memory effect via thermal mechanical treatment. Several experiments were conducted to observe the characteristics of PET such as the crystallization effect and degree of crystallinity when it is subjected to various thermal mechanical methods. This is done to determine the viability of creating coloured PET that would also possess exceptional shape memory properties. After performing numerous experiments such as Dynamic Mechanical Analysis, Differential Scanning Calorimeter, Stretching and heating of PET and Shape Memory Testing, it has been determined that PET with high degrees of crystallinity exhibits colour change as well as exceptional shape memory and shape recovery properties